Testing the Effects of Food Quality, Price Fairness, and Physical Environment on Customer Satisfaction in Fast Food Restaurant Industry - Hanaysha, Jalal (Journal of Asian Business Strategy, 2016)
Building customer satisfaction is considered to be a key priority for business success. Therefore, determining the factors that affect customer satisfaction is important. This paper was designed to examine the effects of food quality, price fairness and physical environment on customer satisfaction in fast food restaurant industry in Malaysian market. The data were collected from 242 customers of international fast food restaurants in east coast Malaysia. The collected data were analysed using SPSS and structural equation modelling (SEM). The findings indicated that food quality has a significant positive effect on customer satisfaction. Moreover, the findings revealed that price fairness and physical environment have significant positive effects on customer satisfaction. These findings provide useful suggestions and guidelines for the policy makers in fast food restaurant industry and confirm the importance of the selected factors in affecting customer satisfaction.